2015
DOI: 10.1371/journal.pone.0139550
|View full text |Cite
|
Sign up to set email alerts
|

Buffalo Cheese Whey Proteins, Identification of a 24 kDa Protein and Characterization of Their Hydrolysates: In Vitro Gastrointestinal Digestion

Abstract: Milk whey proteins are well known for their high biological value and versatile functional properties, characteristics that allow its wide use in the food and pharmaceutical industries. In this work, a 24 kDa protein from buffalo cheese whey was analyzed by mass spectrometry and presented homology with Bos taurus beta-lactoglobulin. In addition, the proteins present in buffalo cheese whey were hydrolyzed with pepsin and with different combinations of trypsin, chymotrypsin and carboxypeptidase-A. When the TNBS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…As shown in Table (2), Cysteine was the predominant amino acid among the total amino acids for both fractions 9.75% and 8.98%, respectively. The results converged with what found Bassan et al(2015) who obtained 14 amino acids from hydrolysates of buffalo milk whey proteins, of which six were basic and Neto et al (2019)who purified seven fractions of peptide from hydrolysates of bovine milk whey proteins that contained 19-10 amino acid. The reason for the variation in the concentrations of amino acids may be due to the hydrolysis conditions in terms of the specificity of the action of the enzyme used the time of hydrolysis, the type of amino acids and their position in the peptide depends on the mechanism of action of the enzyme (Wali et al, 2019).…”
Section: ‫مج(‬supporting
confidence: 87%
“…As shown in Table (2), Cysteine was the predominant amino acid among the total amino acids for both fractions 9.75% and 8.98%, respectively. The results converged with what found Bassan et al(2015) who obtained 14 amino acids from hydrolysates of buffalo milk whey proteins, of which six were basic and Neto et al (2019)who purified seven fractions of peptide from hydrolysates of bovine milk whey proteins that contained 19-10 amino acid. The reason for the variation in the concentrations of amino acids may be due to the hydrolysis conditions in terms of the specificity of the action of the enzyme used the time of hydrolysis, the type of amino acids and their position in the peptide depends on the mechanism of action of the enzyme (Wali et al, 2019).…”
Section: ‫مج(‬supporting
confidence: 87%
“…Although, according to Cervato, Cazzola, and Cestaro (), casein has more antioxidant power than whey proteins like lactoferrin and lactalbumin; it was also proved that the summed antioxidant power of its subunits is higher than of casein as phosphoserine groups become exposed with the subunit's desegregation. Furthermore, Bassan et al () demonstrated a 2.5‐fold increase in the antioxidant capacity of whey proteins due to hydrolysis. Although the ratio between the single proteomic extract antioxidant ability seems to be close along the three antioxidant tests, the fact that in BTMP performing relatively higher in HS might be related to the Fe 2+ /Fe 3+ cycle interference provoked by casein as reported by Cervato, Cazzola, and Cestaro (), making this test less reliable.…”
Section: Resultsmentioning
confidence: 99%
“…Although, according to Cervato, Cazzola, and Cestaro (1999), casein has more antioxidant power than whey proteins like lactoferrin and lactalbumin; it was also proved that the summed antioxidant power of its subunits is higher than of casein as phosphoserine groups become exposed with the subunit's desegregation. Furthermore, Bassan et al (2015) demonstrated a 2.5-fold increase in the antioxidant capacity of whey proteins due to hydrolysis.…”
Section: The Bioactive Components and Antioxidant Activity Of Milk mentioning
confidence: 98%
“…The tertiary structure of GP was destroyed in the process of hydrolysis. It is well known that Ala, Val, Ile, Leu, Phe, Cys, Met, His, Pro, and Lys have free radical scavenging activities (Bassan et al, 2015). In addition, another study indicated that…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 98%